2013
DOI: 10.1063/1.4799385
|View full text |Cite
|
Sign up to set email alerts
|

Optical evidence for donor behavior of Sb in ZnO nanowires

Abstract: High-resolution photoluminescence (PL) experiments show that Sb doped ZnO nanowires exhibit shallow donor bound exciton (D0X) transitions at 3364.3 meV, which is shallower than the well-known In, Ga, Al, and H D0X transitions. The relative intensity of the Sb D0X transition scales with dopant concentration. Temperature dependent PL measurements show that the Sb D0X behaves like other D0X transitions with a thermal activation energy close to the spectroscopic binding energy. No evidence of an ionized donor boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Up to now, we have shown that these complexes should not be suitable to create p-type ZnO. Nonetheless, there are some speculations about their possible presence in experiments 33,34 and so it is interesting to check whether these kinds of defects are likely to be found or not. For the cluster to form, it is essential that their binding en-…”
Section: Stability Of Vacancy Related Complexesmentioning
confidence: 97%
“…Up to now, we have shown that these complexes should not be suitable to create p-type ZnO. Nonetheless, there are some speculations about their possible presence in experiments 33,34 and so it is interesting to check whether these kinds of defects are likely to be found or not. For the cluster to form, it is essential that their binding en-…”
Section: Stability Of Vacancy Related Complexesmentioning
confidence: 97%
“…High-temperature vapor-phase methods have been commonly used to fabricate p-type Sb-doped ZnO, [16][17][18][19] while aqueous chemical methods, especially electrochemical deposition, are rarely employed. A method that introduces the dopant in low-temperature synthesis is attractive because of its low cost and ease of implementation.…”
mentioning
confidence: 99%
“…Other research groups reported the same conclusion, which indicates that Sb atoms have likely doped into the Zn sites in ZnO:Sb NWs. 16,34 In this case, Sb is expected to act as a donor in the ZnO host. However, we cannot decisively conclude that the Sb atoms act as donors in these as-grown ZnO:Sb wires, since these wires have mixed phases.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO:Sb NWs. 16,28 The results were discussed in terms of the Sb dopant mechanism and its lattice position in the ZnO host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation